Pengaruh E-Learning Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas VIII MTsN 5 Magetan - Muhammad Ihyak 'Ulum Muddin; Budi Sasomo; Arum Dwi Rahmawati (Jurnal Karya Pendidikan Matematika, 2022)
This study aims to determine the effect of video-based e-learning on student learning outcomes in learning mathematics in the circle material for class VIII MTsN 5 Magetan. This research was conducted in February 2022. The method used in this study is a quasi-experimental design with a control test. Sampling of data was done by using cluster random sampling technique. The sample of this study amounted to 32 students for the experimental class and 32 students for the control class. Data retrieval using test instruments in the form of multiple choice, data analysis using t test. the results obtained tcount 25.983 > ttable 2.660 with = 1%, which means Ho is rejected. So that the alternative hypothesis (Ha) is accepted, namely that e-learning with videos has an effect on student learning outcomes in mathematics learning material for class VIII MTsN 5 Magetan. It is suggested to the school to provide support and facilities for the development of this video-based e-learning method so that of course it can improve student learning outcomes.Keywords: E-learning; Student Learning Outcomes; Circle